2019
DOI: 10.1016/j.rmed.2019.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Asthma as aetiology of bronchiectasis in Finland

Abstract: Background: By definition bronchiectasis (BE) means destructed structure of normal bronchus as a consequence of frequent bacterial infections and inflammation. In many senses, BE is a neglected orphan disease. A recent pan-European registry study, EMBARC, has been set up in order to better understand its pathophysiology, better phenotype patients, and to individualize their management. Aim: To examine the aetiology and co-morbidity of BE in the capital area in Finland. Methods: Two hundred five patients with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…To address this question, we retrospectively analyzed 234 hospitalized patients aged ≥18 years with non-cystic fibrosis bronchiectasis in the past 8 years in West China hospital. Asthma was considered as the etiology driver to bronchiectasis if it was diagnosed earlier than bronchiectasis, consistent with the definition in the study by Jarkko Mantyla [2]. Our results showed that: among the 32 patients (14%) with bronchiectasis complicated with asthma, 15 patients (6%) were caused by asthma, with higher BMI and worse lung ventilation function (FEV1%, FEV1/FVC, MMEF%) ( Table 1).…”
Section: To the Editorsupporting
confidence: 87%
See 1 more Smart Citation
“…To address this question, we retrospectively analyzed 234 hospitalized patients aged ≥18 years with non-cystic fibrosis bronchiectasis in the past 8 years in West China hospital. Asthma was considered as the etiology driver to bronchiectasis if it was diagnosed earlier than bronchiectasis, consistent with the definition in the study by Jarkko Mantyla [2]. Our results showed that: among the 32 patients (14%) with bronchiectasis complicated with asthma, 15 patients (6%) were caused by asthma, with higher BMI and worse lung ventilation function (FEV1%, FEV1/FVC, MMEF%) ( Table 1).…”
Section: To the Editorsupporting
confidence: 87%
“…Fewer researches have been performed on the coexistence of bronchiectasis and asthma due to the neglects and not enough attentions [1]. Recently, Jarkko Mantyla has investigated the characteristics and outcomes of patients with bronchiectasis in Finland, of which he has specifically addressed bronchiectasis caused by asthma [2]. He found that clinical parameters including body mass index (BMI), highresolution computed tomography (HRCT) ≥ 4 affected lobes, and the number of hospitalization due to exacerbations were higher in the 25 cases (26%) with bronchiectasis caused by asthma compared to those in the 70 patients with bronchiectasis caused by miscellaneous aetiologies.…”
Section: To the Editormentioning
confidence: 99%
“…First, it may support the perspective that bronchiectasis is a consequence of asthma and, therefore, needs time to develop. [ 28 ] Also, it may indicate that the clinical features of bronchiectasis in patients with asthma may be overshadowed by the symptoms of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Only those over 18 years of age and with non-cystic brosis BE were recruited. Details of this cohort have been reported previously [11].…”
Section: Methodsmentioning
confidence: 99%